2019
DOI: 10.1097/md.0000000000016366
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant melanoma of the female genital tract synchronously involving the vulva and uterine cervix

Abstract: Rationale Primary melanomas of the female genital tract are rare and usually occur in the vulva and vagina. Involvement of the cervix, uterus, and ovary are extremely rare. Surgery and adjuvant therapy remain the mainstay of treatment. The majority of patients experience poor long-term survival. This report aimed at highlighting an extremely rare case of primary melanoma of the female genitalia, synchronously involving the vulva and uterine cervix. Patient concerns A 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…It has been reported that although the cervix is usually the origin of MM, almost 20% of all cervical MM are metastatic [ 22 ]. Secondary involvement of the cervix from a MM occurs either with locoregional spread of vaginal/vulvar carcinomas or with hematogenous metastasis of a distant primary MM [ 8 , 42 ]. Multifocal presence of melanoma foci in multiple sites can prove the diagnosis very challenging.…”
Section: Review Of the Literature And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that although the cervix is usually the origin of MM, almost 20% of all cervical MM are metastatic [ 22 ]. Secondary involvement of the cervix from a MM occurs either with locoregional spread of vaginal/vulvar carcinomas or with hematogenous metastasis of a distant primary MM [ 8 , 42 ]. Multifocal presence of melanoma foci in multiple sites can prove the diagnosis very challenging.…”
Section: Review Of the Literature And Discussionmentioning
confidence: 99%
“…The first well-documented case of primary malignant melanoma of the cervix (PMMC) was reported in 1944, by Taylor and Tuttle [ 6 ]. Since then, to this day, less than 100 cases of PMMC have been described [ 7 , 8 ]. The diagnosis of PMMC can be proven very challenging due to the rarity of the disease and also due to the wide variety of cytomorphologic characteristics [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can present as an amelanotic/melanotic nodule/polyp or an ulceroproliferative mass. The patient presents with the complaint of bleeding per vagina/mass per vagina/anaemia …”
Section: Morphology Quizmentioning
confidence: 99%
“…Masson-Fontana and Schmorl's stains can distinguish melanin pigment from many other brown-black pigments and this tumour is positive for S100 (nucleocytoplasmic), HMB45 (cytoplasmic) and Melan-A (cytoplasmic) immunohisto-chemistry. It can be also positive for CD117 (c-kit) and BRAF based on its molecular pathogenesis 2,3.…”
mentioning
confidence: 99%
“…Cervical squamous cell carcinoma (CSCC) is the most common primary tumor in the cervical region; other rare primary tumors include clear-cell carcinoma of the cervix (CCCC) and small-cell carcinoma of the cervix (SCCC), [1][2][3] primary lymphoma of the cervix, 4 cervical choriocarcinoma, 5 sarcoma of the uterine cervix, 6 rhabdomyoma of the cervix, 7 malignant melanoma of the cervix, 8,9 Wilm's tumor of the cervix, 10 and malignant peripheral neurilemmoma of cervical broblasts. 11 Regardless of the type of cervical neoplasm, contact hemorrhage or uor sanguinolentus are the main early clinical manifestations; late clinical manifestations include irregular vaginal bleeding of varying amounts with corresponding symptoms of distant metastasis.…”
Section: Introductionmentioning
confidence: 99%